Team coaching in project management teams at Vodacom South Africa - Ramuada, K R (My University, 2020)
Context: Team coaching is an instrument organisation can employ to provide opportunities for team members to engage towards improved teamwork. Through improved teamwork, team members become motivated to engage on organisational goals. Problem statement: Organisational teams often face challenges which may lead to them being dysfunctional. Such challenges may be in a form of inadequate engagement, unwillingness to share resources, having competing priorities, lack of trust and poor communication between members and across teams. This study utilised team coaching to explore opportunities for teams and team members to optimise their working relationships and improve teamwork amongst them. The study utilised an action research approach to draw knowledge from the experience of team members through interviews. Methodology: Action research was undertaken through a team coaching intervention with nine project managers within the Southern Gauteng region of Vodacom South Africa. By means of qualitative semi-structured interviews, data was collected to establish if team coaching improved teamwork amongst the nine project managers. The collected data was recorded, transcribed and analysed using QDA software (Altas.ti). The key findings: Results suggested that team coaching improves teamwork within a business context. The study demonstrated that team coaching within an action research approach provided opportunities and platform for team members to understand each other’s contribution, skills and expertise necessary for the attainment of the team goal. The study further outlined the importance of relationships, constant communication, collaboration, trust and information sharing in building teamwork between different members of the team. Conclusion: Having an understanding of teamwork by the team and team coach helped direct the engagement of the team towards improved teamwork. Team work improved as the team developed towards an improved level of trust and work commitment. As teamwork improved, members of the team became motivated to commit and support each other towards the team goal.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Business Executive Coaching to the Faculty of Commerce, Law and Management, School of Business Administration, University of the Witwatersrand, Johannesburg, 2020
Keywords: Team coaching; Teamwork; Team effectiveness; SDG-8: Decent work and economic growth